أثر التدريس بالتعلم التعاوني عبر الشبكة الاجتماعية التعليمية إدمودو Edmodo في التحصيل الدراسي لمقرر الحاسب الآلي - الحسن، رياض عبدالرحمن محمد; المطرودي، عائشة بنت صالح (جامعة الإمارات العربية المتحدة - كلية التربية, 2017)
استهدف البحث قياس أثر استخدام استراتيجية التعلم التعاوني عبر الشبكة الاجتماعية التعليمية (إدمودو) في التحصيل الدراسي في مقرر الحاسب الآلي لدى طالبات المرحلة الثانوي. وتكوّن مجتمع البحث من طالبات الصف الأول الثانوي في مدارس المرحلة الثانوية بمدينة الرياض، الفصل الدراسي الأول، للعام 1435/ 1436ه. وقد انتهج البحث شبه التجريبي، وتكوّنت عينة البحث من 71 طالبة من طالبات الصف الأول الثانوي؛ حيث مثّل مجموعة الطريقة التقليدية 22 طالبة، بينما مثّل مجموعة التعلم التعاوني التقليدي 25 طالبة، في حين مثّلت مجموعة التعلم التعاوني عبر الشبكة الاجتماعية التعليمية إدمودو 24 طالبة. وأسفرت نتائج البحث عن وجود فروق ذات دلالة إحصائية بين المجموعات التي درست باستخدام طرق التعلم الثلاث؛ لصالح المجموعة التي درست من خلال الشبكة الاجتماعية التعليمية (إدمودو). وبناءً على نتائج البحث، فإن الأهمية تشجيع استخدام Edmodo في تدريس بعض موضوعات مقرر الحاسب الآلي؛ نظراً لدورها في رفع مستوى التحصيل الدراسي، إضافة إلى سهولة استخدامها من قبل الطالبات. كما تبيّن أنه ينبغي فحص الاستراتيجيات والأساليب التربوية عند استخدام تطبيقات ويب 2.0 (Web2.0) في العملية التعليمية بشكل عام، والشبكات الاجتماعية التعليمية بشكل خاص في الفصول الدراسية؛ لاختيار ما يتناسب مع طبيعة كل منهما؛ لتحقيق النتائج المرجوة من توظيفها.
The purpose of this study was to examine the effect of using a cooperative learning strategy through the educational social network. Edmodo. on academic achievement in a computer course among high school female students. the research population consisted of all first level high school female students in Riyadh, during the first semester of 2014/2015 The study employed a quasi-esperimental approach, with a research sample that consisted of 71 students. with a the traditional control group of 22 students, a group of 25 students that employed traditional cooperative learning. and a group of 24 students that employed cooperative learning through educational social network Edmodo Results of the study showed that in terms of academic achievement, there were significant differences between the three groups favoring the group that used the educational social network: Edmodo. The results of this study illustrated the positive effect of using cooperative learning through educational social network (Edmodo) on academic achievement of female students in first level of high school in a computer course. Based on the findings of the study, some recommendations were introduced, among which The need for promoting the use of cooperative learning strategy through the educational social network Edmodo in computer sources because of its positive effect on academic achievement. Another recommendation was to examine the effect of learning strategies associated with the use of Web2.0 applications. and to choose those applications that show positive effect on students' learning, especially in computer science course
Keywords: شبكات التواصل الاجتماعية -- تكنولوجيا التعليم -- طرق التدريس -- التعلم التعاوني